Eksistensi Kode Etik Notaris dalam Pembatasan Promosi Diri di Era Digital - Ni Kadek Andhina Putri Artini; Made Aditya Pramana Putra (Fakultas Hukum, Universitas Warmadewa, 2026)
This study examines the existence and implementation of the Notary Code of Ethics in regulating self-promotion in the digital era, particularly through social media platforms. The advancement of information technology has transformed how notaries interact with the public, with digital platforms such as Instagram, TikTok, and LinkedIn increasingly used to introduce themselves or their notarial services. However, such practices raise ethical concerns as they contradict Article 4 paragraph (3) of the Notary Code of Ethics, which prohibits any form of professional promotion. This research employs a normative legal method with a literature study approach to analyze the applicable legal provisions within the Notary Law (UUJN) and the Notary Code of Ethics (KEN), as well as to identify the boundaries and legal consequences for notaries who engage in online self-promotion. The results show that notaries are only allowed to use social media for educational and legal awareness purposes, not for commercial interests. Violations of this rule may result in ethical sanctions by the Honorary Council of the Indonesian Notary Association and administrative sanctions by the Notary Supervisory Board. Therefore, it is necessary to update the digital ethics guidelines to provide clearer boundaries for notarial behavior in online spaces, ensuring that integrity, professionalism, and public trust in the notarial profession remain intact amid the rapid development of digital technology.